2019
DOI: 10.1590/s0102-865020190050000005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological modulation of b-adrenoceptors as a new cardioprotective strategy for therapy of myocardial dysfunction induced by ischemia and reperfusion

Abstract: Purpose: To evaluate the cardioprotective response of the pharmacological modulation of β-adrenergic receptors (β-AR) in animal model of cardiac ischemia and reperfusion (CIR), in spontaneously hypertensive (SHR) and normotensive (NWR) rats. Methods: CIR was induced by the occlusion of left anterior descendent coronary artery (10 min) and reperfusion (75 min). The SHR was treated with β-AR antagonist atenolol (AT, 10 mg/kg, IV) 5 min before CIR, and NWR were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 45 publications
(57 reference statements)
2
18
0
Order By: Relevance
“…ECG was monitored and recorded from the beginning of the stabilization period with a commercial acquisition system (AqDados 7.02; Lynx Tecnologia Ltda., Brazil) as reported earlier [9][10][11][12][13] . To assess heart rate, incidences of reperfusion-induced ventricular arrythmia (VA), atrioventricular block (AVB) and lethality (LET), raw data were analyzed with a commercial software package included in the acquisition system (AqDAnalysis 7, Lynx Tecnologia Ltda.).…”
Section: Ecg Recordings and Analysissupporting
confidence: 74%
“…ECG was monitored and recorded from the beginning of the stabilization period with a commercial acquisition system (AqDados 7.02; Lynx Tecnologia Ltda., Brazil) as reported earlier [9][10][11][12][13] . To assess heart rate, incidences of reperfusion-induced ventricular arrythmia (VA), atrioventricular block (AVB) and lethality (LET), raw data were analyzed with a commercial software package included in the acquisition system (AqDAnalysis 7, Lynx Tecnologia Ltda.).…”
Section: Ecg Recordings and Analysissupporting
confidence: 74%
“…Ischemic postconditioning also reduces the formation of free radicals, prolonged opening of MPTP, and ATP deficit production [41,42]. Our studies also indicate that the cardioprotection stimulated by ischemic postconditioning is less efficient than that induced by ischemic preconditioning [42]. In contrast to the beneficial effects observed in animal models, ischemic postconditioning in human using surrogate markers of myocardial salvage has yielded conflicting results [41].…”
Section: Cardioprotective Strategies Against Myocardial Lesions Camentioning
confidence: 97%
“…Studies in animal models of myocardial infarction showed that ischemic postconditioning improved myocardial metabolic recovery and increased myocardial salvage [41,42]. Our studies in animal models of cardiac I/R injury indicate that ischemic postconditioning attenuates ionic imbalance in cardiac cells by reducing the cytosolic and mitochondrial Ca 2+ overload, thus reducing excitation-contraction decoupling and incidence of severe arrhythmias and lethality caused by I/R injury [42]. Ischemic postconditioning also reduces the formation of free radicals, prolonged opening of MPTP, and ATP deficit production [41,42].…”
Section: Cardioprotective Strategies Against Myocardial Lesions Camentioning
confidence: 99%
See 2 more Smart Citations